Aportes del trabajo colectivo a la gestion de la seguridad laboral en situación de riesgo en el àmbito ferroviario - Cecilia De la Garza; Annie Weill-Fassina (Universidade do Porto, 2006)
Ergonomic analyses of the railway field highlight concepts which guide the analysis of collective work. These concepts have been constructed through observation of two risky work processes in the field: rail tracks maintenance and maintenance operations in the electrical device of traffic regulation. Co-action, co-activity, collaboration and co-operation differentiate collective interactions which need coordination and negotiation. The occupational risk management is characterized by connections and regulations on horizontal and vertical levels. Nevertheless, even if ergonomic studies show how collective work should be a safety and a performance criterion they also show how some conditions and lack of safety cannot be recovered. An effective form of prevention should take into account results of this type.